His innocent unwrapped in Iceland - Ashenden, Jackie (Harlequin presents, 2023)
"Jilted at the altar, Isla Kendrick faces an impossible decision: lose her family business or marry the ruthless tycoon trying to take it over. Already in her wedding dress, she reluctantly says "I do." Orion North wants Isla's company...and her! So when the opportunity to save her from a media frenzy arises, he takes it. He whisks her away to his luxurious Icelandic lodge, and the heat burning between them soon takes them to the bedroom. But with tragedy in his past, even their passion might not be enough to melt the ice encasing Orion's heart..."--